ADVANCED PEDAGOGICAL EXPERIENCES IN ORGANIZING AND DEVELOPING THE EDUCATIONAL PROCESS ON THE BASE OF DIGITAL TECHNOLOGIES - Fayzullaeva , Madina (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2023)
This article describes the advanced pedagogical experiences of developed countries in organizing and developing the educational process based on digital technologies. You can also familiarize yourself with the results of research conducted on the organization and development of the educational process based on digital technologies in developed countries such as Germany and Russia. Moreover, by studying the successful experiences of these developed countries, you can get information about the aspects that we can apply to the development of the quality of education in our country based on digital technologies.